Presentation: pay for performance, formulation, implementation and policy success: in low, middle and high income countries - da Cunha Saddi, Fabiana; Peckham, Stephen; Santos Mundim, Pedro (Sociedade e Cultura, 2018)
Low and middle income countries (LMICs), as well as high income countries (HICs), with different politicaleconomic contexts, varying dependence on external financing, as well as in differentiated stages of development of primary health care (PHC), have adopted payment for performance or performance-based financing programs (P4P/PBF). Addressing the reality of different health systems and contexts, in LMICs and HICs, the rationalbased assumptions supporting the design of P4P/PBF programmes have been theoretically questioned by more realistic political, organizational and motivational assumptions. Empirically, they have been challenged by alternative logics and processes arising from comparatively distinctive implementation and (re)formulation processes, diverse unexpected effects/evidence and a recognition of the need to consider adaptations and long-term (sustainable) impacts on health systems. Consequently, P4P/PBF programs have been subject to social sciences, public policy, health policy and health systems research. These analyses have the potential to significantly enrich the debate and knowledge on the operation and impact of P4P/PBF programs and how they could be more effectively designed to support health system performance and strengthening, producing effective/real-world or long-term improvements.